Simulation and calculation of 2, 4, 5, 2', 4', 5' -hexachlorobiphenyl passing from the central axis of single walled carbon nanotube - Mahdavian, Leila (Kuwait Journal of Science, 2017)
The 2, 4, 5, 2?, 4?, 5? -hexachlorobiphenyl (PCB-153) is a high resistant pollutant which cause adverse health effects in recent years. In this study, it is closed and passed into single walled carbon nanotube (8, 8) and is investigated using density functional theory calculations (B3LYP/6-31+G (d)) in terms of complex energy, HOMO/LUMO energy, energy gap (Eg) changes, thermodynamic properties, structural deformation and so on. The results show that, the PCB-153 around SWNT increased the electrical conductivity and sensitivity of SWNT. Calculated electrical and thermodynamic properties show a sudden change in the middle of the tube, where it may act as a trap for the studied pollutant. The results indicated that the nanotube has considerable ability to interact with PCB-153 and cause its degradation. Therefore, for detection and reduction of PCB-153, the nano-filter of SWNT can be used. The total Gibbs free energy and other thermodynamic properties show that, these passings from SWNT can be done favorably and spontaneously.